Differentiated skeletal cells contribute to blastema formation during zebrafish fin regeneration - Sousa, Sara (2018)
The origin of cells that generate the blastema following appendage amputation has been a long-standing question in epimorphic regeneration studies. The blastema is thought to originate from either stem (or progenitor) cells or differentiated cells of various tissues that undergo dedifferentiation. Here, we investigate the origin of cells that contribute to the regeneration of zebrafish caudal fin skeletal elements. We provide evidence that the process of lepidotrichia (bony rays) regeneration is initiated as early as 24 hours post-amputation and that differentiated scleroblasts acquire a proliferative state, detach from the lepidotrichia surface, migrate distally, integrate into the blastema and dedifferentiate. These findings provide novel insights into the origin of cells in epimorphic appendage regeneration in zebrafish and suggest conservation of regeneration mechanisms between fish and amphibians.